Lipoprotein oxidation, genetic expression and polymorphism of Apo A and B gene in patients with coronary artery disease in a Pakistani Punjabi population - Sohail, Hira; Shahzad, Madeeha; Khaliq, Saba; Ijaz, Farhat (Penerbit Universiti Kebangsaan Malaysia, 2024)
Oxidative alterations of lipoproteins and numerous polymorphism locations in the apolipoprotein A1 (APOA1) and B (APOB) genes have been identified as risk factors for cardiovascular events. The aim of the study was to investigate the gene expression and the role of APOA and B gene polymorphisms in coronary artery disease (CAD) and their relationship with lipid profiles, oxidized High Density Lipoprotein (oxHDL), and oxidized Low Density Lipoprotein (oxLDL) in the Punjabi Pakistani population. A total of 200 subjects were included, of which 135 were diagnosed as having CAD and 65 were not. The lipid profile, oxHDL, and oxLDL were measured through the calorimetric method and ELISA, respectively. Quantitative variables represented by mean ± SD for normally distributed data. Gene expression was done on cDNA through Real-time PCR. Genotyping of APOA1 (rs670, rs5069) and APOB (rs693, rs11279109) were performed by PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism), and gel electrophoresis was used for band visualization. Our findings showed that the oxHDL, oxLDL, APOA, B gene expression and Del genotype of APOB rs11279109 was significantly increased in CAD cases. In addition, significant high levels of oxHDL, oxLDL, serum cholesterol, VLDL, TG, and cholesterol/HDL ratio has been shown to be associated with CAD. APOB (rs11279109) has a significant impact on dyslipidemia and exhibit a higher risk of CAD (OR=3.97) while, APOB (rs693), APOA1 (rs670), (rs5069) possesses a lower risk of CAD in the population. Hence, levels of oxHDL and oxLDL as well as ApoA1 and APOB genotyping could be useful in identifying individuals who are at risk of CAD.